Biological, Physiological, and Pharmacological Aspects of Ghrelin - Hiroshi Hosoda; Masayasu Kojima; Kenji Kangawa (Elsevier, 2006)
Abstract.: Ghrelin, identified as an endogenous ligand for the growth hormone secretagogue receptor, functions as a somatotrophic and orexigenic signal from the stomach. Ghrelin has a unique post-translational modification: the hydroxyl group of the third amino acid, usually a serine but in some species a threonine, is esterified by octanoic acid and is essential for ghrelin's biological activities. The secretion of ghrelin increases under conditions of negative energy-balance, such as starvation, cachexia, and anorexia nervosa, whereas its expression decreases under conditions of positive energy-balance such as feeding, hyperglycemia, and obesity. In addition to having a powerful effect on the secretion of growth hormone, ghrelin stimulates food intake and transduces signals to hypothalamic regulatory nuclei that control energy homeostasis. Thus, it is interesting to note that the stomach may play an important role in not only digestion but also pituitary growth hormone release and central feeding regulation. We summarized recent findings on the integration of ghrelin into neuroendocrine networks that regulate food intake, energy balance, gastrointestinal function and growth. Keywords:: ghrelin, growth hormone (GH) secretagogue receptor, GH-releasing peptide, appetite regulation, stomach